Legal Analysis of the Challenges of Child Support Obligations in the Context of Multiparenthood and the Crecer Juntos Law - Trejo, Morena Yamileth Castro (Asian Journal of Science, Technology, Engineering, and Art, 2025)
The incorporation of socio-affectivity in child upbringing, formally recognized by the Crecer Juntos Law (2023) in El Salvador, introduces new legal challenges in relation to maintenance obligations, which have traditionally been grounded in legally established biological kinship. This dogmatic legal and descriptive study examines current legislation, doctrinal perspectives, jurisprudence, and the opinions of family law specialists to assess the normative foundations and existing gaps concerning maintenance responsibilities of affinity parents with socio-affective ties or biological parents lacking legal recognition. The findings reveal the absence of specific regulations requiring such parents to assume maintenance obligations, creating uncertainty in the protection of children’s rights. The study concludes by emphasizing the need for legal reform or, alternatively, judicial interpretation guided by the principle of the best interests of the child. Such measures are essential to adapt the Salvadoran legal framework to the realities of multiparental families and to ensure comprehensive protection of children’s welfare.